Friction-induced vibration of a long flexible shaft with an intermediate support - Hiroki MORI; Takuo NAGAMINE; Hiroshi HORISAKI; Yuichi SATO (Nihon Kikai Gakkai ronbunshu, 2017)
A long flexible shaft such as a lance tube in a soot blower or a drill string in a rotary drilling system exhibits friction-induced vibration resulting in a whirling motion. This paper investigates the whirling motion of a long flexible shaft induced by frictional force and examines the effect of an intermediate support position on the whirling motion. The experimental apparatus investigated has a vertical shaft which rotates at a constant speed by means of an electric motor mounted at the top of the shaft. At the bottom end of the shaft is located a rubber ring so that frictional force acts on the tip of the shaft when the shaft is deflected. Comparing experimental and calculated results we clarify the vibration characteristics, such as whirling frequencies and amplitudes, at various rotational speeds and show the effective position of an intermediate support to suppress shaft vibration.